The role of the chinese dollar peg for macroeconomic stability in China and the world economy - Gunther Schnabl (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2011)
During the 1997/98 Asian crisis and the 2007-2010 world financial and economic crisis, China has proved to be a stabilizer for East Asia and the world. The paper stresses the crucial role of the dollar peg for macroeconomic stability in China. The paper explores the current role of China's nominal exchange rate stabilization as stabilizing factor for China, East Asia and the world economy. Distortions originating in real exchange rate stabilization are identified and are argued to be a risk for global growth perspectives. To prevent further economic and financial turmoil the paper recommends policy coordination between China and the US. The exit from unconventional low interest rate policies in the US combined with the end of real (but not nominal) exchange rate stabilization in China is seen as necessary to stabilize longterm growth in China, East Asia and the US.
urn:nbn:de:gbv:27-20131118-104353-9
Keywords: F15; F31; F33; 330; China; dollar peg; structural distortions; international policy coordination; global imbalances; Stufenflexibilität; Kaufkraftparität; Makroökonomischer Einfluss; China; Ostasien; Welt; Internationale Wirtschaftspolitik; USA